“Our Story is Your Story”: Examining Recent Scholarship on Indigenous and Black Commemorations with a Nova Scotian Focus - Parker, Susan (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2023)
Since the 1960s, there has been a shift in commemoration and museum studies away from settler-only narratives and towards institutional inclusion of Indigenous and Black perspectives. While some critics have condemned institutional misuse of decolonization and diversity, in Nova Scotia there has been meaningful engagement with Black and Indigenous creators and their communities in the province’s institutions and public spaces. This is evidenced by the hiring of Indigenous and Black commemoration professionals, the creation of exhibits and museums/centres that focus on these perspectives, and the ongoing reclamation of public spaces such as parks, streets, and buildings.